Synthesis of Amides from Aliphatic Acids and Amines by using of I2/TBHP at Room Temperature. Issue 4 (25th January 2018) - Sirgamalla, Rambabu; Kommakula, Ashok; Banoth, Sonyanaik; Dharavath, Ravi; Adem, Kurumanna; P, Madhu; Boda, Sakram
Abstract: A novel metal free system of I2 /TBHP for coupling of anilines with various acids leading to amidation has been developed. The reaction possibly proceeds via acetic hypoiodous anhydride formation. Besides, the scope of the method was also extended to thioglycolic acid and phenoxy acetic acids. The reaction is easy to set up, involves mild conditions and proceeds efficiently over a wide range of substrates with excellent functional group tolerance. Abstract : A novel metal free system of I2 /TBHP for coupling of anilines with various acids leading to amidation has been developed. The reaction possibly proceeds via acetic hypoiodous anhydride formation. To avoiding the metal catalysis reaction and improve metal free chemistry research area, amide formation avoiding poor atom economy reagents was voted the highest priority reaction which companies would like to see investigated. The reaction is easy to set up, involves mild conditions and proceeds efficiently over a widespread of substrates with excellent functional group tolerance.